Adenocarcinoma admixed with neuroendocrine carcinoma of the cervix: A case report and review of literature - Yohannis Derbew Molla; Hirut Tesfahun Alemu; Almaz Enku Selamawi; Amare Yeshitla Tesema; Isak Omer Answar; Amanuel Kassa Tadesse (Elsevier, 2024)
A 40-year-old Ethiopian woman presented with a six-month history of non-foul-smelling whitish vaginal discharge. She also reported a one-year history of postcoital bleeding. A pelvic examination revealed a nodular, hard, and fragile cervical mass. In addition, there were nontender, firm nodules in the epigastric, periumbilical, gluteal areas, and thyroid gland. Investigations, including abdominopelvic ultrasound, magnetic resonance imaging, fine-needle aspiration cytology, and immunohistochemistry, confirmed mixed neuroendocrine carcinoma of the cervix with metastasis to the abdominal wall, gluteal area, lumbar vertebrae, and thyroid gland. The patient was started on palliative chemotherapy. Metastatic adenocarcinoma admixed with neuroendocrine carcinoma of the cervix presents a formidable disease phenotype, characterized by complex diagnostic and therapeutic obstacles. Multidisciplinary cooperation among oncologists, radiologists, pathologists, and surgeons is required to refine treatment approaches and improve patient prognoses for this uncommon and intricate malignancy.